Optical processes in solids - Toyozawa, Yutaka, 1926- (Cambridge University Press, 2003)
Light (electromagnetic radiation) is the most powerful tool for probing the quantum mechanical motions of electrons and nuclei within molecules and condensed matter. In this book the author describes the principles of such spectroscopic study with the help of illustrative comparison between theory and experimental studies.